1993
DOI: 10.1111/j.1399-3054.1993.tb00167.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light and temperature on seed dormancy and gibberellin‐stimulated germination in Arabidopsis thaliana: studies with gibberellin‐deficient and ‐insensitive mutants.

Abstract: Derkx, M. P. M. and Karssen, C. M. 1993. Effects of light and temperature on seed dormancy and gibberellin-stimulated germination in Arabidopsis thaliana: studies with gibbereilin-deficient and -insensitive mutants. -Physiol. Plant. 89: 360-368.Effects of light and temperature on gibberellin (GA)-induced seed germination were studied in Arabidopsis thaliana (L.) Heynh. with the use of GA-deficient {gal) mutants, mutants with a strongly reduced sensitivity to GA {gal) and with the recombinant gai/gal. Seeds of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0

Year Published

2002
2002
2008
2008

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 31 publications
1
52
0
Order By: Relevance
“…If the distribution of bioactive GAs is changed under different environmental conditions, the failure of AtXTH31 to be upregulated by low temperature also may be explained by the fact that it is only expressed in cells in which bioactive GAs do not accumulate at a sufficient level to activate it. Although previous physiological experiments have suggested that the tissue sensitivity to GA is modulated by light and temperature signals, the molecular basis for GA sensitivity is not yet clear (Derkx and Karssen, 1993a;Yang et al, 1995;Debeaujon and Koornneef, 2000). Our finding that only a fraction of GA-inducible genes responded to an increase in endogenous GA levels at 48C suggests that a difference in GA sensitivity may be visualized by grouping GA-regulated genes on a large scale based on their response to GA at varying environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the distribution of bioactive GAs is changed under different environmental conditions, the failure of AtXTH31 to be upregulated by low temperature also may be explained by the fact that it is only expressed in cells in which bioactive GAs do not accumulate at a sufficient level to activate it. Although previous physiological experiments have suggested that the tissue sensitivity to GA is modulated by light and temperature signals, the molecular basis for GA sensitivity is not yet clear (Derkx and Karssen, 1993a;Yang et al, 1995;Debeaujon and Koornneef, 2000). Our finding that only a fraction of GA-inducible genes responded to an increase in endogenous GA levels at 48C suggests that a difference in GA sensitivity may be visualized by grouping GA-regulated genes on a large scale based on their response to GA at varying environmental parameters.…”
Section: Discussionmentioning
confidence: 99%
“…In A. thaliana seeds, both light and temperature conditions can alter the amount of GA required for seeds to germinate (Derkx and Karssen, 1993a;Yang et al, 1995;Koornneef et al, 2002). For example, when GA-deficient ga1 mutant seeds were preincubated at 28C for 7 d in the dark, a lower concentration of exogenous GA 4 was sufficient for the mutant seeds to germinate in comparison with the case without cold treatment (Derkx and Karssen, 1993a). This observation indicates that the sensitivity to bioactive GAs may be enhanced by cold treatment (low temperature or long imbibition) in A. thaliana seeds, although the molecular nature that determines GA sensitivity is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…To analyze GA-regulated gene expression, ga1-3 seeds were stratified by imbibing at 4 Њ C in the dark for 48 h and then incubated for 24 h under continuous white light before GA 4 or mock (control) treatment. We included the stratification treatment because it increases tissue sensitivity to exogenous GA (Derkx and Karssen, 1993). Under these conditions, radicle emergence was observed initially at 18 h after GA 4 treatment, whereas the control seeds did not germinate, as shown in Figure 1A.…”
Section: Global Gene Expression Profiles In Response To Exogenous Ga mentioning
confidence: 99%
“…GA biosynthesis de novo is a prerequisite for germination because inhibitors of GA biosynthesis applied during imbibition effectively inhibit the process (Nambara et al, 1991;Derkx and Karssen, 1993). Arabidopsis seeds have a very low germination rate in the dark, while both light and cold promote seed germination, at least partially by stimulating GA biosynthesis (Derkx and Karssen, 1994;Toyomasu et al, 1998;Yamaguchi et al, 1998;Yamauchi et al, 2004).…”
Section: Seed Germinationmentioning
confidence: 99%